2019
DOI: 10.3390/su11123249
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Network Structure and Information Diffusion Behaviors in a Sustainable Fashion Sharing Economy Platform

Abstract: It is important to understand the creative processes of social value networks in terms of the interdependent connections between fashion sharing economy businesses and consumers. In particular, when the similarity in the values of each member is shared in the sub-network, the closeness of the relationships can be further strengthened. In such value chains, the overall process is important because the content, which is originally provided through the distribution process, is reinterpreted from the consumer’s po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Indeed, RTR further represents a new access economy model providing sustainable solutions by offering a more intensive usage of products (Acquier et al, 2017). In other words, this alternative model of clothing consumption would potentially make the fashion industry more sustainable (Eckhardt et al, 2019; Na et al, 2019). Accordingly, this is one of consumers' emergent motivations, founded on the need to make more sustainable (smarter) choices, and as a result of the prospect of increasing the life of each luxury product.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, RTR further represents a new access economy model providing sustainable solutions by offering a more intensive usage of products (Acquier et al, 2017). In other words, this alternative model of clothing consumption would potentially make the fashion industry more sustainable (Eckhardt et al, 2019; Na et al, 2019). Accordingly, this is one of consumers' emergent motivations, founded on the need to make more sustainable (smarter) choices, and as a result of the prospect of increasing the life of each luxury product.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the American platform “RTR” is considered a typical example in this sense (Eckhardt et al, 2019). Other similar platforms are also emerging in Europe (such as the Italian Drexcode and DressYouCan , and the British FrontRow which are so far available only in the London area), due to a sort of social contagion phenomenon that pushes consumers to be more attentive to fashion sharing economy platforms (Na, Kang, & Jeong, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have confirmed evidence of the effect of direct network externalities in the digital environment, digital transformation and the influence of network externalities contribute to an increase in the number of subscribers, a reduction in the number of networks (distortion of market competition), and a decrease in telecommunications prices (Radukić et al, 2020). Previous research on network externalities is generally in the telecommunications sector (Hung et al, 2020;Mouakket & Sun, 2019;Na et al, 2019), social networking sites (Hung et al, 2020;Mouakket & Sun, 2019), relating to digital technology (Lyu, Guo, & Chen, 2023;Pang, Ruan, & Wang, 2023).…”
Section: Various Companiesmentioning
confidence: 93%
“…In such economic lives, individual users, with nearly zero marginal cost, are increasingly involved in the production, consumption and sharing of their commodities and services by joint efforts [7]. Therefore, studies seek insights into sharing economy platforms [8] [9].…”
Section: Introductionmentioning
confidence: 99%